Determination of settlement profiles of foundations composed of weak soils for railway and road embankments, dams, and levees made of earth materials - Shapoval, Volodymyr; Shuminskyi, Valerii; Skobenko, Oleksandr; Konoval, Volodymyr (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article is dedicated to the issue of foundation settlements in railway, road, and other embankments, as well as earth dams and dikes, especially when constructed on weak soils with low deformation modulus. It emphasizes that in such cases, settlements can be comparable to the height of the embankment, requiring settlement profiles to be considered during design. A simple iterative algorithm developed by the authors is proposed for calculating settlement profiles and is recommended for inclusion in the draft Ukrainian State Building Code “Earth Dams. General Requirements.” An example of the algorithm’s application is provided, demonstrating its advantages over conventional graphical and tabular methods. The algorithm ensures simplicity, fast convergence, and results consistent with those obtained using the finite element method. Additionally, the study highlights the limitations of FEM when regulatory guidance on key parameters such as boundary conditions and mesh configuration is lacking. The authors conclude that their proposed algorithm can be effectively implemented in engineering practice for the design of embankments and dams on weak soils with a trapezoidal cross-section.